A brief guide to the genetics of autism spectrum disorders - Karwowska, Joanna; Wawrusiewicz-Kurylonek, Natalia; Tafazoli, Alireza; Posmyk, Renata (Pediatria Polska - Polish Journal of Paediatrics, 2026)
Autism spectrum disorders (ASD) constitute a group of etiologically and clinically heterogeneous neurodevelopmental disorders. Generally speaking, all ASD may be divided into non-syndromic and syndromic types. The former, also known as “pure” or “essential” autism, may have or not identifiable genetic background but there are no other features that constitute a recognizable syndrome. The latter, also referred to as “autism +” occurs with specific phenotypes where autistic features are present among other symptoms. All patients diagnosed with ASD should be offered further genetic counseling involving phenotypical and genotypical diagnosis, pedigree analysis and prognosis of future development. Autism spectrum disorders patients need broader, multidisciplinary care and risk assesment for family members. The aim of this article is to provide a succinct guide on how genetics affects all aspects of ASD care and how to utilize genetics as a general practitioner, pediatrician, or other medical professional working with patients affected by autism spectrum disorder.